Sex-specific differences in children attending the emergency department: prospective observational study - Joany M Zachariasse; Henriette A Moll; Ian K Maconochie; Ewout W Steyerberg; Daan Nieboer; Dorine M Borensztajn; Claudio F Alves; Frank J Smit; Susanne Greber-Platzer; Claudia M G Keyzer-Dekker (BMJ Open)
Objective To assess the role of sex in the presentation and management of children attending the emergency department (ED).Design The TrIAGE project (TRiage Improvements Across General Emergency departments), a prospective observational study based on curated electronic health record data.Setting Five diverse European hospitals in four countries (Austria, The Netherlands, Portugal, UK).Participants All consecutive paediatric ED visits of children under the age of 16 during the study period (8–36 months between 2012 and 2015).Main outcome measures The association between sex (male of female) and diagnostic tests and disease management in general paediatric ED visits and in subgroups presenting with trauma or musculoskeletal, gastrointestinal and respiratory problems and fever. Results from the different hospitals were pooled in a random effects meta-analysis.Results 116 172 ED visits were included of which 63 042 (54%) by boys and 53 715 (46%) by girls. Boys accounted for the majority of ED visits in childhood, and girls in adolescence. After adjusting for age, triage urgency and clinical presentation, girls had more laboratory tests compared with boys (pooled OR 1.10, 95% CI 1.05 to 1.15). Additionally, girls had more laboratory tests in ED visits for respiratory problems (pooled OR 1.15, 95% CI 1.04 to 1.26) and more imaging in visits for trauma or musculoskeletal problems (pooled OR 1.10, 95% CI 1.01 to 1.20) and respiratory conditions (pooled OR 1.14, 95% CI 1.05 to 1.24). Girls with respiratory problems were less often treated with inhalation medication (pooled OR 0.76, 95% CI 0.70 to 0.83). There was no difference in hospital admission between the sexes (pooled OR 0.99, 95% CI 0.95 to 1.04).Conclusion In childhood, boys represent the majority of ED visits and they receive more inhalation medication. Unexpectedly, girls receive more diagnostic tests compared with boys. Further research is needed to investigate whether this is due to pathophysiological differences and differences in disease course, whether girls present signs and symptoms differently, or whether sociocultural factors are responsible.